Selective Activation of Cancer Stem Cells by Size-Specific Hyaluronan in Head and Neck Cancer - Marisa Shiina; Lilly Y. W. Bourguignon (International Journal of Cell Biology)
We determined that human head and neck cancer cells (HSC-3 cell line) contain a subpopulation displaying cancer stem cell (CSC) properties and are very tumorigenic. Specifically, we investigated whether different sizes of hyaluronan (HA) (e.g., 5 kDa, 20 kDa, 200 kDa, or 700 kDa-HA-sizes) play a role in regulating these CSCs. First, we observed that 200 kDa-HA (but not other sizes of HA) preferentially induces certain stem cell marker expression resulting in self-renewal and clonal formation of these cells. Further analyses indicate that 200 kDa-HA selectively stimulates the expression of a panel of microRNAs (most noticeably miR-10b) in these CSCs. Survival protein (cIAP-1) expression was also stimulated by 200 kDa-HA in these CSCs leading to cisplatin resistance. Furthermore, our results indicate that the anti-miR-10 inhibitor not only decreases survival protein expression, but also increases chemosensitivity of the 200 kDa-HA-treated CSCs. These findings strongly support the contention that 200 kDa-HA plays a pivotal role in miR-10 production leading to survival protein upregulation and chemoresistance in CSCs. Together, our findings suggest that selective activation of oncogenic signaling by certain sizes of HA (e.g., 200 kDa-HA) may be instrumental in the formation of CSC functions leading to tumor cell survival and chemoresistance in head and neck cancer progression.